Helix-simulation framework development for assessment of rotorcraft engines - Mohseni, Martina (Cranfield University, 2011)
The inevitable growth of air traffic resulting from the increasing demands on utilization of the aircraft for various purposes has introduced public awareness and concern about the contribution of air traffic towards climate change. The increase of aircraft emissions enhancing the greenhouse effect and decreasing the air quality in general, is no longer considered sustainable and steps are being taken towards the mitigation of this problem. Although a significant research activity takes place in the development of new technologies, the most readily available solution to this problem is seen in applying changes to aircraft operational rules and procedures and in optimizing the flight paths using the aircraft currently in service. The helicopter, although comprising a significantly smaller portion of the aircraft market in comparison with the fixed-winged aircraft, is experiencing the same concerns with respect to the amount of gaseous emissions produced. The helicopter plays a specific and irreplaceable role in the air transportation and it is often being used for purposes where the environmental concerns are secondary (such as during medical rescue operations or during police missions). It is however being increasingly employed for non-urgent operations, such as executive business travel or for the transportation of personnel to and from oil rigs. In all cases, the most readily available solution (and also perhaps the least costly) to lowering the gaseous emissions is to evaluate the helicopter engine performance along a given flight path using a computer program in order to investigate the effect on fuel burn and gaseous emissions. Cont/d.